Mitochondrial Uncoupling Protein 1 Overexpression Increases Yield in Nicotiana tabacum under Drought Stress by Improving Source and Sink Metabolism - Barreto, Pedro; Yassitepe, Juliana E. C. T.; Wilson, Zoe A.; Arruda, Paulo (Frontiers in Plant Science, 2017)
Mitochondrial uncoupling proteins (UCPs) sustain mitochondrial respiration independent of intracellular ATP concentration. Uncoupled respiration is particularly beneficial under stress conditions, during which both photosynthesis and respiration may be impaired. Sustaining carbon fixation during the reproductive phase is essential for plants to develop viable pollen grains and for seed setting. Here, we examined whether UCP1 overexpression (UCP1-oe) would help tobacco plants cope with drought stress during reproductive development. We observed that WT and UCP1-oe plants lost water at the same rate under moderate drought stress, but that UCP1-oe lines regained water faster upon rewatering. UCP1-oe plants maintained higher levels of respiration and photosynthesis and decreased H2O2 content in the leaves during the drought stress period. We examined whether UCP1-oe impacts reproductive tissues and seed production by monitoring the progress of flower development, focusing on the early stages of pollen formation. UCP1-oe lines induced the expression of mitochondrial genes and increased mtDNA content in reproductive tissues, which increased the consumption of carbohydrates and reduced H2O2 content and pollen disturbances. Finally, the beneficial impact of UCP1-oe on the source and sink organs resulted in an increased seed size and number under both control conditions and drought stress.